A variable neighbourhood search for the workforce scheduling and routing problem - Pinheiro, Rodrigo Lankaites; Landa-Silva, Dario; Atkin, Jason (Springer, 2015)
The workforce scheduling and routing problem (WSRP) is a combinatorial optimisation problem where a set of workers must perform visits to geographically scattered locations. We present a Variable Neighbourhood Search (VNS) metaheuristic algorithm to tackle this problem, incorporating two novel heuristics tailored to the problem-domain. The first heuristic restricts the search space using a priority list of candidate workers and the second heuristic seeks to reduce the violation of specific soft constraints. We also present two greedy constructive heuristics to give the VNS a good starting point. We show that the use of domain-knowledge in the design of the algorithm can provide substantial improvements in the quality of solutions. The proposed VNS provides the first benchmark results for the set of real-world WSRP scenarios considered.